2013
DOI: 10.1021/jp408729g
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study on the NMR Chemical Shifts of Molecules Confined in Carbon Nanotubes

Abstract: Large magnetic shielding has been experimentally observed on certain organic molecules, regardless of their intrinsically different chemical natures, when they are confined within the carbon nanotubes. We investigated the underlying physics of the shielding effect by employing a series of density functional theory calculations on various molecule-confined-in-CNT systems. Particularly, the effects of the intermolecular interaction and the ring current of the CNTs on the chemical shifts of the confined molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…With the help of density functional theory (DFT) calculations, Dd is found to be related to the intrinsic electronic structures of carbon, carbon structure and pore size distribution. 103,181,182 Studies show that this so-called nucleus-independent chemical shift (NICS) allows for distinguishing the ion confined within carbon pores, as well as the ion population. [181][182][183][184][185] In 2006, Lee et al used ex situ magic angle spinning (MAS) NMR to study ion adsorption in porous carbon in organic electrolytes.…”
Section: Nuclear Magnetic Resonance Spectroscopy (Nmr)mentioning
confidence: 99%
See 1 more Smart Citation
“…With the help of density functional theory (DFT) calculations, Dd is found to be related to the intrinsic electronic structures of carbon, carbon structure and pore size distribution. 103,181,182 Studies show that this so-called nucleus-independent chemical shift (NICS) allows for distinguishing the ion confined within carbon pores, as well as the ion population. [181][182][183][184][185] In 2006, Lee et al used ex situ magic angle spinning (MAS) NMR to study ion adsorption in porous carbon in organic electrolytes.…”
Section: Nuclear Magnetic Resonance Spectroscopy (Nmr)mentioning
confidence: 99%
“…103,181,182 Studies show that this so-called nucleus-independent chemical shift (NICS) allows for distinguishing the ion confined within carbon pores, as well as the ion population. [181][182][183][184][185] In 2006, Lee et al used ex situ magic angle spinning (MAS) NMR to study ion adsorption in porous carbon in organic electrolytes. 186 Solid state 11 B NMR spectra could distinguish between the BF 4 À anions located outside and inside the pores at the open-circuit voltage (OCP), charged, and discharged stages.…”
Section: Nuclear Magnetic Resonance Spectroscopy (Nmr)mentioning
confidence: 99%
“…For studying ring current effects, this is most commonly done through calculation of the nucleus-independent chemical shift (NICS). 59 In The NICS approach has been used to explore ring current shielding effects on species confined within well-defined carbon nanostructures such as nanotubes 60 , 61 , 62 and fullerenes. 63 These studies…”
Section: Solid-state Nmr Of Adsorbed Species As a Probe Of Electrode mentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39] This effect has also been investigated in theoretical studies, where it has been shown that the characteristic shi in frequency for adsorbed species arises due to the circulation of delocalised electrons in the carbon surface, which results in a locally reduced magnetic eld. [40][41][42][43] This so-called nucleus-independent chemical shi (NICS) therefore provides a useful means by which to identify ions conned within carbon micropores and can in principle be used to obtain information about their local chemical environments such as pore diameter and local curvature of the carbon surface. Indeed, we have recently shown how NMR can identify adsorbed ions in model supercapacitor electrodes comprising pieces of microporous carbon lm soaked with a NEt 4 -BF 4 /ACN electrolyte.…”
Section: Introductionmentioning
confidence: 99%